2014
DOI: 10.1007/s00198-014-2649-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use and 10-year incident fracture risk: the population-based Canadian Multicentre Osteoporosis Study (CaMoS)

Abstract: Summary-We used data from a large, prospective Canadian cohort to assess the association between selective serotonin reuptake inhibitors (SSRIs) and serotonin and noradrenaline reuptake inhibitors (SNRIs) and fracture. We found an increased risk of fractures in individuals who used SSRI or SNRI, even after controlling for multiple risk factors.Introduction-Previous studies have suggested an association between SSRIs and increasing risk of fragility fractures. However, the majority of these studies were not lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 43 publications
5
64
0
Order By: Relevance
“…The mechanism of action of different classes of antidepressants appears to produce different skeletal effects: several rodent and human observational studies have reported negative skeletal effects with serotonergic antidepressants. There have been several recent studies linking SSRI/SNRI drugs to increased fragility in humans, which are consistent with our results (Warden et al, 2010(Warden et al, , 2008Bonnet et al, 2007;Lanteigne et al 2015;Moura et al, 2014).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The mechanism of action of different classes of antidepressants appears to produce different skeletal effects: several rodent and human observational studies have reported negative skeletal effects with serotonergic antidepressants. There have been several recent studies linking SSRI/SNRI drugs to increased fragility in humans, which are consistent with our results (Warden et al, 2010(Warden et al, , 2008Bonnet et al, 2007;Lanteigne et al 2015;Moura et al, 2014).…”
Section: Discussionsupporting
confidence: 95%
“…The mechanism by which antidepressants impact bone health appears to be primarily via serotonergic pathways (Shea et al, 2013). Functional 5-hydroxytryptamine (5-HT) transporters and receptors are present in osteoblasts, osteocytes and osteoclasts, and stimulation of these receptors influences bone cell activities (Moura et al, 2014). The mechanism of action of different classes of antidepressants appears to produce different skeletal effects: several rodent and human observational studies have reported negative skeletal effects with serotonergic antidepressants.…”
Section: Discussionmentioning
confidence: 98%
“…A higher risk of fractures has previously been reported in SSRI users, with a duration-and dosedependent effect; the higher the doses, the longer the use and the higher the risk [10,11,14,42,43]. However, most studies using administrative data, could not fully control for important confounders such as osteoporosis and related factors, e.g., use of anti-osteoporosis drugs and supplements (e.g., calcium, vitamin D or hormone therapy in women) and smoking.…”
Section: Discussionmentioning
confidence: 91%
“…Dose and duration of SSRIs also contribute to fracture risk, with both an early increased risk (<6 weeks) and a late risk associated with prolonged use for more than 3-5 years [Richards et al 2007;Eom et al 2012]. A recently published large 10-year longitudinal cohort study [Moura et al 2014] examined fracture risk in SSRI and SNRI users over the age of 50. They found SSRI and NSRI use increased fragility fractures with a hazard ratio (HR) of 1.88 (95% CI 1.48-2.39).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%